A tecnologia informacional e o trabalho do professor de direito: o SAJ da PUC Minas de Contagem - Odil de Lara Pinto (2010)
The dissertation verses on the impact of information and communicational technology, mediated by the Virtual Office (E.A) of the Judiciary Assistance Service in attending the vulnerable population of the city of Contagem. There is a concentration on the control of lawsuits, since after the "virtual" creation of the respective "clients" file, the whole process movement process of the specific case should show in the Virtual Office System. The accountability process mediated by information technology thus begins. The control of the student in supervision of his case, control of the professor over the student and at times, the control of the student over the professor, as well as the accountability of the professors by the coordination of the institution. The methodology applied was quantitative, a structured questionnaire being used followed by the required tabulation of the data obtained. At a subsequent moment of the research, there was a structured questionnaire used in an attempt to hear the subjects out, whose words were duly taped and transcribed, always insuring, due ethical confidence. All process movement should appear in the virtual system of the Virtual Office. (E.V) and, once in the system, time will be now, the time of urgency, minimal time, in temporal time. Urgency manifests itself, thus, as a perversion of time. The perversion which shows itself through the sentiment of impotence, of never being able to get away from urgency as well as the even more urgent solutions to the case to be solved, characterizing the closeness of the vicious circle to which both students and professors are tied, that is, duty, the obligation of instilling an intense rhythm of the professional teaching work of Law, as well as that of the worker in general. The presence of information technology and its mediation, by means of the Virtual Office (E.V), in the teaching work of the Law professor quashes the professionalizing technological rationality of the teaching worker permeated in the economy of time with a maximum of productivity, which is a characteristic of the capitalist mode of production. Information technology, the expression of modernity in the domain of immaterial work assists the instrumental control of the human being over objects. This control translates a power relation of the human subject over the material world which is reduced to the category of an object through human subjectivity. Herein lies the problem of the use, the mediation of information technology in the immaterial work context, since all human work consists in the manipulation of information, above all that of intellectual work, in which information simultaneously constitute the process, the matter and the result of its work. Our research confirmed that the technological rationality used in the Virtual Office contributes to the intensification of teaching work, according to subjects of research. A The pathology of time limits was manifested by juridical process limits as well as by limits assigned to the Professor to be met in the Virtual Office.